The relationship between upper cross syndrome posture and shoulder disability - Made Bagus Krishna Wiranatha; I Putu Yudi Pramana Putra; Putu Ayu Sita Saraswati; Gede Parta Kinandana (Physical Therapy Journal of Indonesia, 2024)
Background: Crossfit is a high-intensity sport that has the potential for injury risk. Upper cross syndrome posture increases muscle tension in the upper region, resulting in pressure on the neck and shoulders, pain, numbness, and decreased body function. This research aimed to determine the relationship between upper cross syndrome posture and shoulder functionality among cross fitter in Bali. Methods: The study was an analytical observational study with a cross-sectional design conducted from November 2023 to February 2024 with the main target population for this study being CrossFit practitioners at Crossfit Bali who experienced upper cross syndrome posture. The exclusion criterion is a history of a shoulder injury. The sample size was 50 people who had upper cross syndrome posture. This study used purposive sampling and the measurement of upper cross syndrome posture was used the REEDCO posture test Tragus to Wall test and Shoulder Pain and Disability Index. Results: It was found that 35 people had forward heads, 30 people had rounded shoulders, 33 people had uneven shoulders, and 8 people had tilted heads. Results of the decrease in functional shoulder using the SPADI test showed a mild decrease in 47 people (94%) and a moderate decrease in 3 people (6%). Results of the correlation test with the Spearman rho test, which is 0.647, it is stated the results are not related. Conclusion: There was no relationship between upper cross syndrome and functional shoulders in CrossFit in Bali.